MENTORING AS A TOOL FOR PROFESSIONAL DEVELOPMENT OF TEACHERS - Dzerviniks, Jānis (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2017)
The terms 'mentor' and 'mentoring' are frequently used in the field of business, however, nowadays they are topical in general education as well. In Latvia, the teacher mentor profession has been included in the Classification of Occupations since 2012, which means that teachers, who have acquired the rights to carry out mentoring at educational institutions, can be paid for teacher mentor work hours. However, mentoring is most often a life's calling for teachers rather than a position with financial cover. A wish to identify the pedagogical potential of mentoring in the field of teachers' professional development determined the topic of the research. The research reflected in the paper includes the analysis of scientific literature, analytic judgements based on previously conducted research, as well as the results of the interview of teacher mentors and author's personal pedagogical experience.